Learning and memory : a comprehensive reference - Byrne, John H. (Elsevier, 2008)
"Presents a summary of the present state of research in the neurobiology and psychology of learning and memory. Covers topics such as the neurochemistry and neurobiology of learning at the cellular and synaptic levels, systems neurobiology, the study of remarkable capabilities in animals (such as homing), ethological and behavioristic analyses, mechanisms, psychology, and disorders of learning and memory in humans."--Publisher description